Numerical simulation study on the ultimate injection concentration and injection strategy of a proppant in hydraulic fracturing - Wu, Jianfa; He, Yuting; Zeng, Bo; Huang, Haoyong; Gui, Junchuan; Guo, Yintong (Frontiers in Energy Research, 2024)
The injection volume and the distribution of proppant inside the fracture will have a direct impact on the stimulation effect of fracturing. In this study, a new proppant transport model was established based on Euler method. In this model the proppant plugging element allows fluid to pass through. And the proppant plugging process was successfully simulated based on this model. The proppant transport and ultimate injection concentration under different injection modes were discussed. The numerical simulation results indicate that compared with the strategy of concentration is constant, the strategy of concentration stepwise increasing can make the proppant distribution in the fracture more uniform. The strategy of injection with concentration stepwise increasing and periodic injection with concentration stepwise increasing can increase the injection volume of proppant by 25%. In the fracture network, a 67% increase in the number of branch fractures resulted in a 17% increase in the maximum proppant injection volume. If the branch fracture width is reduced by 50%, the maximum proppant injection volume is reduced by 17%.